Effects of Chiropractic Care on Strength, Balance, and Endurance in Active-Duty U.S. Military Personnel with Low Back Pain: A Randomized Controlled Trial - Vining, Robert; Long, Cynthia R; Minkalis, Amy; Gudavalli, M Ram; Xia, Ting; Walter, Joan; Coulter, Ian; Goertz, Christine M (The journal of alternative and complementary medicine (New York, N.Y.), 2020)
To investigate whether chiropractic care influences strength, balance, and/or endurance in active-duty United States military personnel with low back pain (LBP). This study employed a prospective randomized controlled trial using a pragmatic treatment approach. Participants were randomly allocated to 4 weeks of chiropractic care or to a wait-list control. Chiropractic care consisted of spinal manipulation, education, advice, and reassurance. Naval Air Technical Training Center branch clinic at the Naval Hospital Pensacola Florida. One hundred ten active-duty military personnel 18-40 years of age with self-reported LBP. Isometric pulling strength from a semisquat position was the primary outcome. Secondary outcomes were single-leg balance with eyes open and eyes closed, and trunk muscle endurance using the Biering-Sorensen test. Patient-reported outcomes such as pain severity and disability were also measured. Outcomes were measured at baseline and 4 weeks. Linear mixed-effects regression models over baseline and 4 weeks were used for analysis. Participants had mean age of 30 years (18-40), 17% were female, 33% were non-white, and 86% reported chronic LBP. Mean maximum pulling strength in the chiropractic group increased by 5.08 kgs and decreased by 7.43 kgs in the wait-list group, with a statistically significant difference in mean change between groups ( = 0.003). Statistically significant differences in mean change between groups were also observed in trunk muscle endurance (13.9 sec, = 0.002) and balance with eyes closed (0.47 sec, = 0.01), but not in balance with eyes open (1.19 sec, = 0.43). Differences in mean change between groups were statistically significant in favor of chiropractic for LBP-related disability, pain intensity and interference, and fear-avoidance behavior. Active-duty military personnel receiving chiropractic care exhibited improved strength and endurance, as well as reduced LBP intensity and disability, compared with a wait-list control.